Clinical Features and Prognostic Factors of Primary Intracranial Malignant Fibrous Histiocytoma: A Report of 8 Cases and a Literature Review. Issue 3 (September 2016) - Li, Peng; Zhou, Qiangyi; Yang, Zhijun; Wang, Zhenmin; Li, Shiwei; Wang, Xingchao; Wang, Bo; Zhao, Fu; Liu, Pinan
Objective: Primary intracranial malignant fibrous histiocytoma (MFH) is rare. We describe the detailed clinical features of 8 cases and fully review the literature to evaluate several prognostic factors. Methods: Eight patients with pathologically confirmed primary intracranial MFH were retrospectively reviewed. We searched PubMed for relevant articles with the term "intracranial malignant fibrous histiocytoma". Results: Of the 8 patients, 4 were men and 4 were women. Three patients had received previous radiotherapy. The age of the patients ranged from 19 to 69 years, with a median age of 48 years. Most tumors could be totally resected; and only 1 tumor was subtotally resected. Six patients received postoperative radiotherapy and 3 patients received postoperative chemotherapy. Most patients died within the first year after surgery; and only 1 patient was still alive on the date of the last follow-up. We reviewed the literature and included a total of 46 patients in the Kaplan-Meier survival analysis. Young patients (less than 30 years old) seemed to have a better prognosis and survival rate than older patients (more than 30 years old) (log-rank test, P = 0.008). However, sex (P = 0.675), extent of resection (P = 0.934), postoperative radiotherapy (P = 0.592), and postoperative chemotherapy (P = 0.424) did not affect patient prognosis. Conclusions: The prognosis of MFH is usually poor, and most patients die within the first year after surgery. Younger MFH patients (less than 30 years old) seem to have a better prognosis and improved survival compared to older patients.